Designing a Website-Based Digital Library Information System at SMK Negeri 1 Tanjung Pura - Alviona Marsya; Darmeli Nasution (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This research aims to design a website-based Digital Library Information System for SMK Negeri 1 Tanjung Pura to improve the management and accessibility of learning resources for students and faculty. The current library system at the school is still manual, which limits the efficiency and effectiveness of accessing books, articles, and other educational materials. The proposed system is designed to provide a user-friendly interface for searching, borrowing, and managing digital library resources. Using web development technologies such as HTML, CSS, JavaScript, and PHP, the system integrates a database to store and retrieve information on available resources. This system is expected to enhance the library’s services by enabling online access to resources, improving the efficiency of administrative tasks, and supporting a more effective learning environment. The system's design considers usability, security, and scalability to ensure its long-term viability and relevance in the educational context of SMK Negeri 1 Tanjung Pura.